REDUCTION OF EMISSION EXHAUST GASES FOR COMPRESSION IGNITION ENGINE BY USING DIESEL– ETHANOL BLEND - لطيف عبدالله مثنى; حريجة عبد الحسين; لطيف عبد الله مهند (Journal of Engineering and Sustainable Development, 2018)
Demand for alternative fuel became very important things because of the volatility of oil prices in the world as well as to reduce the amount of polluting gases to the environment. This study aims to determine the impact of the diesel – ethanolblend on the performance of the diesel engine and the percentages of pollution resulting from it. The research was conducted experimentally to study the effect of variable rates of diesel - ethanol fuel (5%, 8%, 10%), at varying values ​​of engine speed ranged between (1100-2600rpm), and the values ​​of a variable load on this engine were (2 - 10N.m), the different engine performance were measured and the most harmful gases exhaust to the environment that is a carbon monoxide (CO), non-burned hydrocarbon (HC) and nitrogen oxides (NOx) were measured too. Through the obtained results showed that the indicated power and brake power are increasing directly proportional with the engine speed and decreasing with increasing the percentage of ethanol in the blend, as well as with the indicated thermal efficiency and exhaust gas temperature, but at high loads this increasing will be less, while increasing break specific fuel consumption when increasing the percentage of ethanol in the blend. It was found that diesel-ethanol blend gives delay long ignite values ​​because of its high resistance to self-ignition compared with diesel fuel, so the maximum pressure in the cylinder decreases when using diesel-ethanol blend compared to fuel diesel because the temperature of the combustion ...